Incorporating hydrogels into fingermark development: indicative viscosities for preserving ridge detail on paper surfaces. Issue 44 (28th October 2022) - Clarke, Kristen T.; Hopkins, Scarlet L.; Gee, William J.
Abstract : Viscous hydrogels show promise as a green forensic method of delivering chemical developers while preserving fingerprint ridge detail. Abstract : Water-based fingermark development treatments for paper have long been held back by loss of ridge detail due to diffusion. Viscous hydrogels (≥2224 cP) show promise as a green method of delivering chemical developers that inhibits diffusion, thereby preserving fingermark ridge detail. This is demonstrated here with starch and xanthan gum hydrogels applied to iodine-fumed fingermarks.